Analisis Kebijakan Presiden Duterte Melakukan Extrajudicial Killing Dalam Memberantas Narkoba di Filipina Berdasarkan Statuta Roma 1998 - Fivi Fajar Iryana; Handojo Leksono (Faculty of Law Universitas Sebelas Maret, 2018)
This study aims to analyze the extrajudicial killing measures conducted by President Duterte may or may not be qualified as an international crime and the application of individual responsibility principles against President Duterte under International Criminal Law, especially the Rome Statute 1998. This research is normative legal research is prescriptive and applied with statute approach, case approach, and conceptual approach. The legal substance of this study uses primary legal materials and secondary legal materials. Technique of collecting legal material through literature study or document study, which then analyzed by using deduction technique based on deductive reasoning method. The research results show that extrajudicial killing action in the Philippines which is one of the effects of President Duterte’s ‘war on drugs’ policy has violated international human rights, namely ICCPR Article 6 paragraph (1) on the right to life, Article 9 paragraph (1) on freedom and personal safety, and ICSECR Article 12 on the right to health. In addition, the Philippines also violates the National Human Rights, namely the Constitution of the Republic of Philippines 1987 Chapter III Article 14 paragraph (1) on equal protection before the law. Such human rights violations may be qualified as crimes against humanity under the Rome Statute 1998 for fulfilling the elements of crimes against humanity in accordance with Article 7 of the Rome Statute 1998. Thus the principle of individual responsibility under Article 28 of the Rome Statute 1998 on Responsibility of Commanders and Other Superior can be applied against President Rodrigo Duterte.